Tai Chi Chuan Exercise Improves Lung Function and Asthma Control through Immune Regulation in Childhood Asthma. (23rd October 2019) - Liao, Pei-Chun; Lin, Han-Hong; Chiang, Bor-Luen; Lee, Jyh-Hong; Yu, Hsin-Hui; Lin, Yu-Tsan; Yang, Yao-Hsu; Li, Pei-Yi; Wang, Li-Chieh; Sun, Wei-Zen
Abstract : Background . Tai Chi Chuan (TCC) is an exercise of low to moderate intensity with key features of mindfulness, structural alignment, and flexibility to relax the body and mind in adults. Our previous study showed that TCC could improve the quality of life (QoL), pulmonary function, and fractional exhaled nitric oxide in asthmatic children. We further investigated whether the benefits induced by TCC were associated with immune regulation. Method . Six- to twelve-year-old children diagnosed with mild to severe persistent asthma for at least one year according to the Global Initiative for Asthma guidelines were enrolled from a tertiary pediatric allergy center in Taiwan. Asthmatic children were divided into two groups based on their choice: (1) the TCC group had a 60-minute TCC exercise session once weekly led by an instructor and (2) the control group kept their original activity levels. All other exercises were encouraged as usual. Pulmonary function tests, laboratory tests, standardized pediatric asthma QoL questionnaire (PAQLQ(S)), and childhood asthma control test (C-ACT) were performed before and after the TCC program (12 weeks). Data on medications and exacerbations were collected from medical records. Results . There were no differences between the TCC ( n = 25) and control ( n = 15) groups at baseline, except that the C-ACT showed significantly lower results in the TCC group (p = 0.045 ). After 12 weeks, the number of leukocytes (p = 0.041 ) and eosinophils (p = 0.022 ) decreased, while regulatory T cells increased significantly (p = 0.008 ) only in the TCC group. Lung functions (FEV1 and PEFR) were significantly improved in both the TCC (p < 0.001 ) and control (p = 0.045 and 0.019, respectively) groups, while the PAQLQ(S) and C-ACT (p < 0.001 ) showed improvement only in the TCC group. Moreover, compared to the control group, the exacerbations within 12 weeks after the study were significantly decreased in the TCC group (p = 0.031 ). After multiple regression by a conditional forward method, the factors that were significantly associated with exacerbation within 12 weeks after study is the practice of TCC and exacerbation within 24 weeks before study (p = 0.013 and 0.015, respectively) after adjusting for age, sex, asthma severity, PEF, FEV1, C-ACT, PAQLQ(S), and medication score at baseline. Conclusion . TCC exercise may improve pulmonary functions, asthma control, and QoL and prevent exacerbations in asthmatic children through immune regulation. Further research on detailed mechanisms is mandated.